Physical stability test of liquid facial soap formulation of citronella extract (Cymbopogon nardus L.) - Setyowati, Endang; Nisa, Nur Fadhillah Hidayatul; Nasriyah; Nilawati (Jurnal Ilmiah Farmasi, 2025)
Background: Citronella (Cymbopogon nardus L.) is one of Indonesia’s most fertile herbal plants. It contains antibacterial compounds and can be used as a liquid facial wash. With the correct formulation, citronella extract facial wash can effectively remove dirt and sebum on the face and prevent the growth of acne-causing bacteria.Objective: This research aims to obtain the optimal formula for citronella extract liquid facial wash.Method: Citronella extract was formulated into the liquid facial wash with concentrations of 9, 18, and 24%, and then the physical stability of the preparation was tested for 3 weeks. After that, the results are compared with the standards that have been set.Results: The citronella extract contained saponins, polyphenols, and flavonoids. The three liquid facial wash formulations made from citronella grass extract had a thick, liquid texture, a unique smell, a brown color, a viscosity range of 948-2,506 cPs, a potential hydrogen range of 4.8–5.97, an adhesive test range of 1.2-2.58 seconds, a foam height range of 0-107 mm, and a spreading power of 5–6.4 cm.Conclusion: The conclusion is that all stability tests for citronella extract liquid facial wash formulations meet the requirements except for the foam height test. The formulation that differs in extract concentration by 24% is the most optimal.